2018
DOI: 10.1111/clr.13305
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of titanium particles and biocorrosion on implant survival and complications? A critical review

Abstract: Objectives To compile the current evidence regarding the association between the release of titanium particles and biologic complications of dental implants. Material and methods This is a critical review. We searched the literature using the terms “corrosion,” “allergy,” “hypersensitivity,” or “particles” together with “titanium,” “Ti,” “TiO2.” The bibliographies of identified publications and previously published review articles were scanned to find additional related articles. We included clinical studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
154
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 134 publications
(231 reference statements)
1
154
0
4
Order By: Relevance
“…There is limited scientific evidence to support an effect on the course of peri-implant diseases. Furthermore, the procedure leads to the release of titanium debris in vast quantities to the peri-implant tissues, which may have adverse biological effects [38]. For this reason, only the supracrestal parts of the implant exposed following bone loss due to peri-implantitis, or as a result of mucosal recessions should be carefully considered for implantoplasty therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited scientific evidence to support an effect on the course of peri-implant diseases. Furthermore, the procedure leads to the release of titanium debris in vast quantities to the peri-implant tissues, which may have adverse biological effects [38]. For this reason, only the supracrestal parts of the implant exposed following bone loss due to peri-implantitis, or as a result of mucosal recessions should be carefully considered for implantoplasty therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium particles have been reported to cause degenerative changes in peri-implant tissue where they are phagocytosed by macrophages and neutrophils activated as part of the biological response (Fage et al, 2016;Noronha Oliveira et al, 2018;Thomas et al, 2013). Although recent studies have demonstrated a potential of titanium particles to cause inflammatory reactions in peri-implant tissue, hard evidence for a causal relationship is yet to be provided (Fretwurst, Nelson, Tarnow, Wang, & Giannobile, 2018;Mombelli, Hashim, & Cionca, 2018). Whether zirconia implants may cause immunological reactions similar to titanium (Cionca, Hashim, Cancela, Giannopoulou, & Mombelli, 2016) or no such effects (Siddiqi, Duncan, De Silva, & Zafar, 2016) continues to be debated.…”
Section: Introductionmentioning
confidence: 99%
“…In contact with biological fluids, these particles can dissolve and generate Ti ions . Although Ti particles and ions may be found in healthy and diseased peri‐implant surrounding tissues, higher concentrations of these products have been found in peri‐implantitis sites . In addition, recent studies have suggested that both Ti particles and ions can influence the pathogenesis of peri‐implantitis …”
Section: Introductionmentioning
confidence: 99%
“…11 Bacterial accumulation around dental implants triggers inflammation and can lead to corrosion and release of Ti products on the surrounding tissues. 6 Although the effect of Ti products on human cells is widely recognized, their microbiological effect has only been tested in models using planktonic growth of few bacterial species. [14][15][16] The disadvantage of this type of methodology is not mimicking the complex structure/composition of the oral biofilm.…”
mentioning
confidence: 99%